Bone mineral metabolism during gestation and its effects on maternal bone mass - Vidal, Luis (2008)
Pregnancy and lactation are periods of high calcium demand for skeletal growth and maternal milk production. Approximately 25-30 g of calcium are transferred to the fetus during pregnancy, and breast-feeding mothers secrete 200-240 mg/day of calcium in breast milk every day. During pregnancy, major physiologic adaptations include increased both calcium intestinal absorption and rate of maternal bone turnover; during lactation, there is a contribution of renal calcium conservation, but temporary maternal bone demineralization is the main mechanism to meet calcium requirements. Data on bone mineral density assessed by dual energy x-ray absortiometry (DXA) are sparse mainly due to concern about potential risk of radiation exposure to the fetus. Other radiation-free techniques like quantitative ultrasound have been used to assess maternal bone mass changes during pregnancy. Maternal bone loss mainly depending on trabecular areas during pregnancy has been described. Calcium supplements reduce maternal skeletal-bone turnover as evaluated by bone resorption markers during pregnancy and seem to have beneficial effects on maternal bone loss. Longitudinal studies with repeated measurements of quantitative ultrasound during pregnancy have found decrease in bone loss in pregnant women with adequate calcium intake or supplementation.